The Association between Cervical Exam after Ripening with Foley Balloon Catheter and Outcomes of Nulliparous Labor Induction - Battarbee, Ashley N.; Palatnik, Anna; Peress, Danielle A.; Grobman, William A. (American Journal of Perinatology, 2018)
Objective Evaluate the association between cervical examination after ripening with Foley catheter and labor induction outcomes.Materials and Methods In this retrospective cohort, nulliparous women with singleton, viable gestation undergoing cervical ripening with Foley catheter were compared based on cervical status after catheter removal or expulsion: favorable (modified Bishop score ≥ 5) or unfavorable (score < 5). Bivariable and multivariable analyses were performed to determine whether cervical examination postripening was associated with time to delivery and chance of vaginal delivery.Results A total of 774 women were eligible. Women with favorable examination postripening had lower body mass index (BMI) and more favorable admission cervical examination. The frequency of vaginal delivery was higher in women with favorable cervical examination postripening (57.9% versus 46.8%, p < 0.01). Median durations from Foley removal or expulsion to complete dilation (8.6 h versus 11.5 h) and vaginal delivery (10.4 h versus 13.2 h) were shorter for women with favorable cervical examination postripening (p < 0.001). In multivariable analysis, favorable examination postripening remained associated with vaginal delivery (adjusted odds ratio 1.39, 95% confidence interval 1.04–1.87), and time to vaginal delivery (adjusted hazard ratio 1.39, 95% confidence interval 1.13–1.70).Conclusion A favorable modified Bishop score after cervical ripening with Foley balloon catheter is associated with higher chance of vaginal delivery and shorter labor duration.
Keywords: Bishop score; Foley balloon catheter; labor induction; nulliparous